Analysis of Dominant Factors And Financial Performance of BPD: Mediated Model of Non-Performing Credit - Atang Hermawan (International Publisher (YAPENBI), 2023)
This study aims to find out and obtain the results of an analysis of the dominant factors both internal and external factors in the Financial Performance of Bank BPD with a non-performing loan mediated model. The method used in this research is descriptive and verification method. The sampling technique used saturated or census sampling to obtain a sample of 26 Regional Development Banks (BPD) from 2014 to 2018. The analytical method used is panel data regression with the pooled least squares approach. The results of the study show that the Capital Adequacy Ratio (CAR), Loan Asset Ratio (LAR), Loan to Deposit Ratio (LDR), SBI Interest Rate, Gross Domestic Product (GDP) have an effect on non-performing loans (NPL) , while Bank Size (Size) and Exchange Rate (Exchange Rate) have no effect. Furthermore, non-performing loans have no effect on financial performance as proxied by Return on Assets (ROA).